Abro1 maintains genome stability and limits replication stress by protecting replication fork stability - Shengfeng Xu; Xiao Y. Wu; Ling Wu; A. Pons Castillo; Jianxin Liu; Erin Atkinson; Atanu Paul; Dan Su; Katharina Schlacher; Yoshihiro Komatsu; M. James You; Bin Wang (2017)
Protection of the stalled replication fork is crucial for responding to replication stress and minimizing its impact on chromosome instability, thus preventing diseases, including cancer. We found a new component, Abro1, in the protection of stalled replication fork integrity. Abro1 deficiency results in increased chromosome instability, and Abro1-null mice are tumor-prone. We show that Abro1 protects stalled replication fork stability by inhibiting DNA2 nuclease/WRN helicase-mediated degradation of stalled forks. Depletion of RAD51 prevents the DNA2/WRN-dependent degradation of stalled forks in Abro1-deficient cells. This mechanism is distinct from the BRCA2-dependent fork protection pathway, in which stable RAD51 filament formation prevents MRE11-dependent degradation of the newly synthesized DNA at stalled forks. Thus, our data reveal a new aspect of regulated protection of stalled replication forks that involves Abro1.